1965
DOI: 10.1021/ac60227a005
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Study of Nitrite and Oxide in Sodium Nitrate-Potassium Nitrate Eutectic Melts.

Abstract: The quantitative electrochemical determination of nitrite ion in fused alkali metal nitrate melts is discussed, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…On substituting nitrogen with COz, a new cathodic wave appears whose half-wave potential was found to be again E l l , = -0.32 f 0.01 V a t 513 K: see curves b and c in Figure 4. This is in agreement with the overall electrode process COz + H20 + 2e = C032-+ Hz ( 7 ) different from the one observed (12) in melts saturated with dry C 0 2 C 0 2 + NOT + 2e = C03?-+ NO< (8) which occurs a t more negative potentials ( ( E 1 , J 8 = -0.52 V a t 510 K).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…On substituting nitrogen with COz, a new cathodic wave appears whose half-wave potential was found to be again E l l , = -0.32 f 0.01 V a t 513 K: see curves b and c in Figure 4. This is in agreement with the overall electrode process COz + H20 + 2e = C032-+ Hz ( 7 ) different from the one observed (12) in melts saturated with dry C 0 2 C 0 2 + NOT + 2e = C03?-+ NO< (8) which occurs a t more negative potentials ( ( E 1 , J 8 = -0.52 V a t 510 K).…”
Section: Resultssupporting
confidence: 78%
“…The traces of nitrite ions always present in a "pure" melt (8,9) were eliminated to avoid overlapping of nitrite and carbonate electrooxidation waves: this was done by direct injection into the melt of concentrated nitric acid which thermally decomposes (20) giving origin to nitrogen dioxide in the solution. The disappearance of the nitrite wave, due to the reaction ( 2 1 ) (2) was controlled voltammetrically, as well as the absence of OHtraces.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Additionally, it has been reported in previous work that increased nitrite content of the salt mixture results in enhanced oxidative behavior, and that nitrite is continuously formed as time proceeds due to thermal and electrochemical degradation. 16 Stainless steel 316 and Incoloy 800H both experienced significantly lower weight gain rates than Alloy 4130 at 400 and 500…”
Section: Exposure Study Resultsmentioning
confidence: 94%
“…Because the thermal decomposition of nitrates at higher temperatures (>400°C) gives rise to nitrite ions, a study of the electrochemical behavior of nitrite was essential to monitor any interaction with other aerial components. Unfortunately, although the electro-oxidation of nitrite ions has been reported previously (20)(21)(22)(23)(24)(25)(26)(27) , no measurements have been made at temperatures higher than 350°C. Careful examination of these studies showed inconsistencies in the results, but all worke'rs agree that nitrite ions are oxidized according to (28) However, Arvia et al (26,27) indicated that such a mechanism represented only part of the story because the electrode material played a prominent role..…”
Section: Methodsmentioning
confidence: 99%